(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To sssess the current status of pre-hospital care in traffic accident patients at Military Hospital 175. Methods: Cross-sectional descriptive study the current status of pre-hospital care on 846 which was caried out on trauma patients after traffic accidents. Trauma patients wereadmitted to the Emergency Department, Military Hospital 175 from March 2023 to October 2023. Research variables were collected according to the study medical record form and then statistically analyzed. Results: The majority of traffic accident patients received on-site first aid (70.45%), of these 52.01% of trauma patients received first aid properly and 47.99% did not receive first aid properly. There was 37.12% of trauma patients were transported to the Emergency Department, Military Hospital 175 properly and safely; meanwhile, the majority (62.88%) were not transported properly. Conclusion: Most of trauma patients from traffic accidents received first aid measures pre-hospital, but the rate of first aid and proper transportation was still low.